In vivo confocal imaging of fast intrinsic optical signals correlated with frog retinal activation - Zhang, Qiu-Xiang (2011)
Using freshly isolated animal retinas, we have conducted a series of experiments to test fast intrinsic optical signals (IOSs) that have time courses comparable to electrophysiological kinetics. In this Letter, we demonstrate the feasibility of in vivo imaging of fast IOSs in intact frogs. A rapid line-scan confocal ophthalmoscope was constructed to achieve high-speed IOS recording. By rejecting out-of-focus background light, the line-scan confocal imager provided the resolution to differentiate individual photoreceptors in vivo. Rapid confocal imaging disclosed robust IOSs with time courses comparable to retinal electroretinogram kinetics. High-resolution IOS images revealed both positive (increasing) and negative (decreasing) light responses, with subcellular complexity.